POTRET IDENTITAS SAINS MAHASISWA CALON GURU SD: MASIHKAH GENDER MENJADI PENGHALANG? - Siti Zahra Mulianti Natsir (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Science identity is a psychosocial construct that influences students’ interest, perseverance, and engagement in scientific activities. This study aims to analyze the differences in science identity between male and female students using the Mann–Whitney U test. The instrument employed was a science identity scale consisting of three domains: appreciation of scientific perspectives, positive attitudes toward the science community, and concern for environmental issues. The sample consisted of 19 male students and 20 female students from the Primary School Teacher Education (PGSD) program at a teacher education institution in Makassar. The sample was selected using a random sampling technique. The results showed that there were no significant differences in domains D1, D2, and D3. However, a significant difference was found in the total science identity score (p = 0.035), with female students scoring higher than male students. These results indicate that gender differences in the science identity of prospective elementary school teachers emerge cumulatively rather than within specific dimensions. This finding highlights the need for inclusive strategies to support science identity development for all PGSD pre-service teachers, particularly by providing recognition and equitable opportunities for engaging in science learning without gender bias.